(untitled) (International Journal of Innovative Technologies in Economy, 2020)
Summarized in the article are different opinions of researchers regarding the essence of creativity, presenting different interpretations of the notion of “creative management”. Two types of management are described: ”traditional and creative”. The main elements of the system of creative management are characterized. described were the basic stages of evaluating and analyzing of the state of the system of creative management. The article contains coefficients , characterizing the system of enterprise’s creative management, particularly the coefficients of target matching, target realization, the coefficients of consciousness and productivity of subjects, coefficients of targets realization, the coefficient of subjects discipline, the coefficient of realization of creative ideas, the coefficient of intensity of taking creative solutions, the coefficient of rationality of creative solutions, the coefficient of completeness of information provision of management subjects in creative management and the coefficient of communication development. Defined were the instruments for a manager to apply at implementing creative management at an enterprise.